Del triunfo de la Revolución Cubana a la Asamblea General de la O.E.A. en San Pedro Sula - Contreras, Gerardo (2012)
The OAS charter proclaimed a norm of democratic governance which validated the importance of representative democracy as central to peace and stability in the Western Hemisphere.  While this normative commitment made sense in the era of the good neighbor policy, multilateralism and non intervention, U.S. abandonment of these principles since the Eisenhower Administration weakened the norm and created a crisis of legitimacy in the OAS through its treatment of Guatemala in 1954 and Cuba in 1962.  The approval of Resolution VI in the meeting of foreign affairs ministers in 1962, excluding Cuba from the OAS because of its government’s Marxist ideology was a case of counterproductive institutionalization of the democratic governance norm.  This article explores the cycle of regress and renewal of the democratic governance norm through an examination of the OAS treatment of Cuba since 1962 to the 39th OAS General Assembly in San Pedro Sula in 2009.